Analisis Pendapatan Istri Nelayan Pada Usaha Warung Makan di Kawasan Wisata Pantai Binasi Kelurahan Binasi Kecamatan Sorkam Barat Kabupaten Tapanuli Tengah Provinsi Sumatera Utara - Lusi Angelia Ritonga; Eni Yulinda; Trisla Warningsih (Jurusan Sosial Ekonomi Perikanan, 2020)
This research aimed to analyze the household income of fisherman and determine the contribution of fishing household members in the coastal tourism area Binasi, Binasi Village, West Sorkam District, Central Tapanuli Regency, North Sumatra Province. The method used is a survey method by observing directly to the object of research by collecting data through a questionnaire, determining the respondents using the census method, amounting to 10 fisherman households residing and his wife working as a businessman in the coastal tourism area of ​​Binasi. The results showed fishermen's income from fishing business with an average net income of IDR. 1,586,134 / month while the source of fisherman's wife's income from the non-fisheries sector of food stalls in the coastal area was IDR. 1,283,341 / month, with an average income of fishermen households that was IDR 2,869,475 / month and the contribution given by fisherman was 55,20% while contribution from wife was 44,80%.